The Qumran Manuscripts of Lamentations: A Text-Critical Study. By Gideon. R. Kotzé - Knight, Gwen (The journal of theological studies, 2014)
As the title suggests, this is a rigorous analysis of the four oldest extant Qumran Lamentation manuscripts (3QLam, 4QLam, 5QLama and 5QLamb). This is in line with the Studia Semitica Neerlandica series and is aimed at students and scholars interested in textual criticism, ancient translations, and their history and particular cultural setting as witnesses to the Book of Lamentations. Kotzé's purpose in this major investigation is to establish the differences and difficulties between the Qumran texts and the Masoretic text. In addition he aims to bring new theories to the interpretation of the Lamentations text by a better understanding of the original Hebrew texts.